(3cJGH aj GdWHs - (3eMeO(B( (3aJMG (B) (3Hf jMji (B( (3GdTHj (B) (3GdgTJhcj (B( (3GdMGeOj(B)(3,J (B1163 (3g` s ((3HSeGf Hf GHQGgje Hf eMeO Hf ehOhQ s)
(3ChdgG (B:s
(3eHJhQ GdChd hChd eGajg (B: (3GSJaGOI GdefGaY ddCOhjI HhMi ddCfHjGA Ch GdJLQjH HTQWg GdPi gh GdJcQGQ s
(3BNQgG (B:s
(3YGOI dUZGQ ChdGOge , hbGd (B: (3EPG bdYJ GdTYQI RGd GdVQQ s
(3GdfSNI HgG MhGTs
(3LGA GSe GdeDda Ydi fSNI CNQi aj GdecJHI GdYGeI HGdQHGW QGLY agQS GdeNWhWGJ GdYQHjI HGdQGHGW (B356/2 (3hPcQ CYdi GdUaMI Gdhdi(B: (3WH GdYdGeI SjOi eMeO jMji GdTHi GdShSjs
(3YdjgG JYGdjbs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs